Cuenca, realidad virtual - Concepción Rodríguez Ruza; Adela Mª Muñoz Marquina; Aurelio Lorente González; Virginia Cañas Córdoba (Virtual Archaeology Review)
This project, Cuenca, realidad virtual, was created so that the key periods of the historical evolution of Cuenca could be explained, where the Islamic Cuenca, Christian Cuenca and Cuenca in the 18th Century are comprised. The reconstruction of these different ages is represented by different routes through a threedimensional environment by means of this application .In order to be put into practice, 3D geometries, 3D polygon models, texturin, 3D illumination and threedimensional geometries animation of all of these elements have been implemented. Virtual visits are introduced by some texts, hearings, plans, archive and current pictures. These routes allow the visitor to get to know the past of this town through a recreational and easy going method